DAYA TARIK PESAN PERSUASIF UNTUK MENINGKATKAN MOTIVASI BERWIRAUSAHA PADA MAHASISWA: Analisis pada Mata Kuliah Kewirausahaan - Israwaty Suriady; Fitriani Puspa Ningsih; Giska Mala Rahmarini (Kinesik, 2022)
Unemployment is one of the problems faced by Indonesia. The Central Statistics Agency (BPS) stated that as of August 2021 the number of unemployed had reached 9.1 million people. The highest unemployment rate is actually created by the educated group. The phenomenon of low interest and motivation for entrepreneurship today is being taken seriously by various parties, both the government, the world of education, the industrial world, and society. The large number of unemployed and the lack of interest in entrepreneurship have become auto criticism of the role of universities. The purpose of this study was to determine the attractiveness of messages in entrepreneurship education courses which are expected to increase students' interest in choosing entrepreneurship as a career choice. This research uses descriptive research type. The sample technique used was purposive sampling and 5 students who had taken the subject of entrepreneurship were selected as informants in this study. The appeal of the message is the theory used in this study. Data analysis used qualitative methods. The results of the study show that messages containing fear are felt by students in material that illustrates the difficulty of getting a job as a civil servant or in a private company, the ever-increasing unemployment rate and the challenges and competition going forward in finding work. Emotional messages are formed through efforts to develop positive feelings in students when they become entrepreneurs.